2022
DOI: 10.2147/ijwh.s372328
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Based on SEER Database for Predicting Prognosis in Patients with Mucinous Ovarian Cancer: A Real-World Study

Abstract: Mucinous ovarian cancer (MOC) is a rare histological type of EOC. In order to guide the clinical diagnosis and management of MOC patients, we constructed and verified a nomogram for the estimation of overall survival in patients with MOC. Patients and Methods: We collected 494 patients with MOC diagnosed from 2010 to 2015 in SEER database, and the following main inclusion criteria were used: (1) patients whose MOC was confirmed by pathology; (2) patients without a history of primary other cancer. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…They observed that ET treatment led to phosphorylation and inactivation of the inhibitory kinase WEE1, along with upregulation of CDC25A phosphatase, highlighting the role of WEE1 in ET-dependent mitogenesis. PYHIN1, a member of the PYHIN (pyrin and HIN domain-containing) protein family, exerts complex functions ranging from tumor suppression to tumor promotion, depending on the specific tumor (Tong et al, 2019;Ding et al, 2022). Its involvement in DNA damage repair, cell cycle regulation, immune responses, and inflammation contributes to its multifaceted role in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that ET treatment led to phosphorylation and inactivation of the inhibitory kinase WEE1, along with upregulation of CDC25A phosphatase, highlighting the role of WEE1 in ET-dependent mitogenesis. PYHIN1, a member of the PYHIN (pyrin and HIN domain-containing) protein family, exerts complex functions ranging from tumor suppression to tumor promotion, depending on the specific tumor (Tong et al, 2019;Ding et al, 2022). Its involvement in DNA damage repair, cell cycle regulation, immune responses, and inflammation contributes to its multifaceted role in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, advances in molecular profiling technologies have paved the way for the discovery of potential shared biomarkers for cancer survival and AMI prediction (Zhao et al, 2022). Transcriptomics has emerged as a powerful tool for comprehensively analyzing gene expression patterns and identifying differentially expressed genes associated with both diseases (Wang et al, 2009;Ding et al, 2022). Integration of multiomics data, combining transcriptomics with other molecular profiling techniques such as genomics and proteomics (Reel et al, 2021), holds even greater potential in unraveling the complex interplay between cancer and AMI.…”
Section: Introductionmentioning
confidence: 99%
“…All statistical analyses were conducted using R software (version 4.1.2). Detailed descriptions of the statistical methods are provided in previous sections and references (19,20). Statistical significance was set at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, all patients were divided into high and low risk groups according to the cut-off value of risk score. For nomogram, based on our previous references, we utilized the regplot package (v1.1) to develop a nomogram that combined risk scores with significant clinical indicators identified by multivariate Cox regression analysis ( 19 ). To validate the prognostic predictive ability of the newly generated scores, we employed several packages, including survminer (v3.3-1), timeROC (v0.4), rms (v6.3-0), and rmda (v1.6).…”
Section: Methodsmentioning
confidence: 99%